Laparoscopic Repair of Diaphragmatic Rupture: A Case Report with Radiological and Surgical Correlation. (20th August 2017) - Nguyen, Patrick; Davis, Bonnie; Tran, Daniel D.
Abstract : The leading cause of diaphragmatic rupture is penetrating abdominal trauma, including gunshot- and stab-related wounds; however, diaphragmatic rupture can also result from blunt trauma to the abdomen. The diagnosis can be difficult to make as the physical examination may be unremarkable, and imaging, that is, a conventional chest X-ray and/or CT imaging, may initially fail to reveal the injury. Failure to recognize diaphragmatic rupture can result in a delayed presentation, sometimes years later, with a potential catastrophic outcome. Therefore, prompt and swift diagnosis is critical to avoid this potential harmful scenario. Traditionally, repair is performed through a laparotomy or a thoracotomy incision. Owing to the many advances made in minimally invasive surgery, not only has laparoscopy become the modality of choice to diagnose diaphragmatic rupture due to its high degree of sensitivity and specificity, but it can provide simultaneous therapeutic intervention as well. We report a case of laparoscopic repair of a diaphragmatic rupture in a 22-year-old female who sustained blunt abdominal trauma during a motor vehicle accident.